The Longitudinal Impact of HIV+ Parents' Drug Use on their Adolescent Children - Lester, Patricia (2009)
The impact of parental substance use on the emotional and behavioral adjustment of their adolescent children was examined over five years. A representative sample of 220 parents with HIV (PWH) and 330 adolescent children in New York City were repeatedly assessed. Some parents never used marijuana or hard drugs over the 5 years (nonusers). Among those who were users, substance use varied over time. PWH who used substances during a specific 3-month period were classified as active users and those who abstained from substance use were classified as inactive users. Longitudinal regression analyses were used to analyze the impact of variations in patterns of substance use over time on their adolescent children's emotional adjustment and behavioral problems. PWH relapse exacerbated adolescent substance use, trouble with peers, and adolescent emotional distress. Even time-limited reductions in parents' substance abuse can have a significant positive impact on their adolescent children's emotional and behavioral adjustment. Interventions which address parental substance use among PWH should be developed to ameliorate the impact of substance use relapse on their adolescents.